2020
DOI: 10.3389/fspor.2020.00053
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Isometric Wrist Flexion and Extension Maximal Voluntary Contractions Similarly Impair Hand-Tracking Accuracy in Young Adults Using a Wrist Robot

Abstract: Due to their stabilizing role, the wrist extensor muscles demonstrate an earlier onset of performance fatigability and may impair movement accuracy more than the wrist flexors. However, minimal fatigue research has been conducted at the wrist. Thus, the purpose of this study was to examine how sustained isometric contractions of the wrist extensors/flexors influence hand-tracking accuracy. While gripping the handle of a three-degrees-of-freedom wrist manipulandum, 12 male participants tracked a 2:3 Lissajous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 97 publications
3
8
3
Order By: Relevance
“…We hypothesized that a larger deficit would be observed in all tracking metrics for the extension fatigue session compared to the flexion fatigue session due to known anatomical and functional differences between the flexors and extensors. This was not observed in our previous study on an isometric fatiguing task, which may have been due to the previous isometric fatiguing protocol being matched with a dynamic task, whereas the present study matches a dynamic fatigue protocol with a dynamic task (Forman D. A. et al, 2020 ). We also hypothesized that males would be more proficient at tracking than females due to the reported sex differences for force steadiness (Brown et al, 2010 ; Jakobi et al, 2018 ).…”
Section: Introductioncontrasting
confidence: 86%
See 2 more Smart Citations
“…We hypothesized that a larger deficit would be observed in all tracking metrics for the extension fatigue session compared to the flexion fatigue session due to known anatomical and functional differences between the flexors and extensors. This was not observed in our previous study on an isometric fatiguing task, which may have been due to the previous isometric fatiguing protocol being matched with a dynamic task, whereas the present study matches a dynamic fatigue protocol with a dynamic task (Forman D. A. et al, 2020 ). We also hypothesized that males would be more proficient at tracking than females due to the reported sex differences for force steadiness (Brown et al, 2010 ; Jakobi et al, 2018 ).…”
Section: Introductioncontrasting
confidence: 86%
“…Eighteen young, recreationally active adults were recruited: 8 females (Height: 168 ± 6 cm, Weight: 67 ± 14 kg, Age: 23 ± 2 years) and 10 males (Height: 179 ± 9 cm, Weight: 81 ± 12 kg, Age: 25 ± 3 years). Our sample size was similar to previous groups investigating comparable outcome measures, including Forman D. A. et al ( 2020 ), Huysmans et al ( 2008 ), Emge et al ( 2013 ), Missenard et al ( 2008a , b ), and Jaric et al ( 1997 , 1999 ). All participants were self-reported right-hand dominant and free from known neurological or musculoskeletal disorders of the upper extremities.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Recently, we explored this topic by examining how sustained wrist flexion and extension MVCs influenced dynamic hand-tracking accuracy [9]. In this study, hand-tracking was performed on a three-degrees-of-freedom wrist manipulandum before and after a sustained MVC, which ceased when participants could no longer maintain 25% of their baseline MVC force.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the wrist extensors must function at a higher percentage of maximal activation [11,17], and this is the primary reason why the extensors fatigue more rapidly than the flexors [18]. It was therefore suggested that sustained wrist flexion may have induced fatigue in both muscle groups [9]. Thus, if wrist extensor fatigue does impair wrist joint stability, and subsequently tracking accuracy, that instability would have been present following each fatigue session.…”
Section: Introductionmentioning
confidence: 99%